A hybrid solar-battery-supercapacitor based camping lamp - Yaccub, Amir; Mustafa, Farahiyah; Mohd Asry, Anis Maisarah; Norjali, Rasida; Sim, Sy Yi; Zambri, Nor Aira (FAZ Publishing, 2020)
Lighting is an essential and insufficient lighting will make us difficult to see things clearly and performing almost all our daily activities. There will be a problem for activities like camping or hiking because there is no electricity and a camping lamp usually used to provide light. Previous product of camping lamp use only rechargeable battery as the supply and it is unconvincing to use the camping lamp for a long time as it only stays on for a few days. A camping lamp that can be charged by exposing to the sunlight can be the solution to overcome this problem. This study is enhancing the features of camping lamp using solar energy as the source to recharge the energy storage devices. There are two types of energy storage devices namely rechargeable battery and supercapacitor that function as the backup charging system. The supercapacitor harvest solar energy from the camping lamp itself so that the product can be recharge when there is no sustainable sunlight. The product will give a huge benefit to anyone who love to do outdoor activity.